2024
DOI: 10.1021/acscatal.3c05059
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Efficient Biocatalyst for the Phosphoribosylation of Antiviral Pyrazine-2-carboxamide Derivatives

Evgeniy A. Zayats,
Ilya V. Fateev,
Yulia A. Abramchik
et al.

Abstract: The development of technologies for the efficient synthesis of innovative antiviral compounds remains an important challenge for modern biotechnology, especially in the context of the recent COVID-19 pandemic. One of the drugs that is currently in the research spotlight for potential anti-SARS-CoV-2 activity is the purine mimetic prodrug compound T-705, also known as favipiravir. Along with a similar compound, T-1105, the activation of T-705 is limited by the low rate of phosphoribosylation, mediated by an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…16–19 The studies of the mechanism of action of T-705 revealed its activity as a nucleobase analogue. 20,21 It is converted into ribonucleoside triphosphate intracellularly and acts on viral RNA-dependent RNA polymerase. 22,23 Such a transformation produced by nucleophilic substitution at the tautomeric NH moiety of T-705 can proceed easily for the keto-tautomer.…”
Section: Introductionmentioning
confidence: 99%
“…16–19 The studies of the mechanism of action of T-705 revealed its activity as a nucleobase analogue. 20,21 It is converted into ribonucleoside triphosphate intracellularly and acts on viral RNA-dependent RNA polymerase. 22,23 Such a transformation produced by nucleophilic substitution at the tautomeric NH moiety of T-705 can proceed easily for the keto-tautomer.…”
Section: Introductionmentioning
confidence: 99%